(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Individual choice of the immunomodulatory drugs and rational combination of physical therapeutic factors with immunomodulatory therapy is an important task of clinical immunology. At present empiric approaches to administration of the immunomodulatory drugs in immunotherapy of oncologic patients. The investigation of the role of some molecules in realization of positive treatment effect of the combined therapy of patients with uveal melanoma allowed to develop new approaches to search and development of complex schemes of treatment with the use of immunomodulators. The imvestigations of the molecular mechanisms of the immunocompetent cell activation will allow to develop pathogenetically substantiated approaches to treatment of patients with uveal melanoma. Objective. To study the influence of the drug amixin in vitro on the expression of molecular markers of lymphoid cell activation CD7+, CD25+, CD38+, CD45+, CD54+, CD95+, CD150+ in patients with uveal melanoma. Material and methods. The level of the expression of molecular markers of lymphocyte activation was studied using immunohistochemical PAP- method with the help of the panel of monoclonal antibodies CD7+, CD25+, CD38+, CD45+, CD54+, CD95+, CD150+ before and after cultivation with the drug amixin. The study was conducted in vitro with lymphocytes of the peripheral blood of patients with uveal melanoma (N=30). The statistic processing was made by the computer program Statistica 6.0 using Newman-Keuls criterium. Results. The studies made on the effect of the drug amixin in vitro on the expression state of molecular markers of lymphocyte activation in the peripheral blood of patients with uveal melanoma revealed authentic increase of the expression indices CD7+, CD25+, CD54+, CD95+ after using the above-mentioned drug. The level of the expression CD7+ reliably increased from 26.4±3.8 % to 34.1±2.6 % (p<0.05); CD25+ — from 19.4±3.3 % to 28.8±3.1 %, (p<0.01); CD54+ — from 18.3±5.1 % to 32.7±2.2 %, (p<0.01); CD95+ -from 24.2±6.3 % to 36.5±5.4 %, (p<0.05). Conclusion. The method of the investigation of the influence of immunomodulatory drugs on the molecular profile of lymphocytes in the peripheral blood developed in the immunology laboratory of SI» Filatov’s Institute of eye diseases and tissue therapy of NAMN of Ukraine» can be used in the clinical practice for choosing adequate immunocorrection therapy. The interferon inductor amixin can be applied in the process of combined therapy (photocoagulation + ?-application therapy) in patients with uveal melanoma or immunocorrection.